Distributional limits of the Shortnose Guitarfish, Zapteryx brevirostris (Rhinopristiformes: Trygonorrhinidae) - An update - Xavier, Lilian G. (2024)
The Shortnose Guitarfish, Zapteryx brevirostris, is endemic to the Southwest Atlantic and its geographic range is commonly reported from southeastern Brazil to northern Argentina. However, range limits are imprecise or inconsistent in some cases. These inconsistencies were solved in this study based on 1,363 specimens collected since 1865. These records were obtained from scientific collections, a systematic review of literature, and an onboard observation database. According to the data collected in this study, the known northernmost distributional limit of the species lies at the mouth of the Doce River, northern Espírito Santo State, in Southeastern Brazil (19ºS). As for the other extreme of its range, the known southernmost distribution limit refers to the Falkland Islands (Malvinas) (53°S). This represents more than 2,000 km of coastline geographic range extension — in comparison to the previous known southernmost range limit for this species. The geographical range of Z. brevirostris seems to follow biogeographic patterns operating at an ecosystem level in which biotic (especially in the north) and abiotic factors (especially in the south) play a role in imposing limits to its distribution range.